2019
DOI: 10.1111/mve.12378
|View full text |Cite
|
Sign up to set email alerts
|

Chewing lice from high‐altitude and migrating birds in Yunnan, China, with descriptions of two new species of Guimaraesiella

Abstract: In total, 366 birds representing 55 species in 24 families and eight orders, were examined for chewing lice (Phthiraptera: Amblycera, Ischnocera) in two high‐altitude localities in Yunnan Province, China. In Ailaoshan, almost all of the birds examined were resident passeriforms, of which 36% were parasitized by chewing lice. In Jinshanyakou, most birds were on migration, and included both passerine and non‐passerine birds. Of the passerine birds caught in Jinshanyakou, only one bird (0.7%) was parasitized by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…How many lice can an observer expect to find on a sample of birds? In broad but short-term surveys of many bird species in Peru (24) and China (20,54), host species had 0.4-1.9 species of lice and 0.5-4.2 louse individuals per bird specimen. In long-term studies in Canada with large numbers of specimens per host, 16 bird species hosted 1-4 species of lice (mean of 2.3), with a mean abundance of 93 lice per specimen, 67% having some lice, and a mean intensity of 188 lice per infested bird (47,49,50,52).…”
Section: Abundance Of Chewing Lice On Their Avian Hostsmentioning
confidence: 99%
“…How many lice can an observer expect to find on a sample of birds? In broad but short-term surveys of many bird species in Peru (24) and China (20,54), host species had 0.4-1.9 species of lice and 0.5-4.2 louse individuals per bird specimen. In long-term studies in Canada with large numbers of specimens per host, 16 bird species hosted 1-4 species of lice (mean of 2.3), with a mean abundance of 93 lice per specimen, 67% having some lice, and a mean intensity of 188 lice per infested bird (47,49,50,52).…”
Section: Abundance Of Chewing Lice On Their Avian Hostsmentioning
confidence: 99%
“…Since bird body mass was unrelated to elevation, this covariation is not rooted in differences in body mass at different elevations. Gustafsson et al (2019) also reported an unusually high prevalence of lice on small passerines at high geographic elevations. They suggested that this may reflect differences in environmental factors such as ambient relative humidity, which is known to affect some louse assemblages (Bush et al , 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Since highelevation habitats may provide more limited food resources to hummingbirds than low-elevation ones, aggressive interactions with body-to-body contacts (both within and between species) may be more frequent, providing more opportunities for horizontal transmission of lice (Johnson and Clayton, 2003) at high elevations. This may be analogous to the effect of forming mixed species feeding flocks in passerines (Gustafsson et al, 2019). Alternatively, birds' energy constraints may be stricter at higher elevations so that birds may allocate less time and energy to antiparasitic behaviours like preening.…”
Section: Discussionmentioning
confidence: 99%
“…Birds were caught and fumigated for lice in several localities across South China during 2012-2021 (Figure 2) using standard mist nets (net size: 2 m × 6 m; 2 m × 12 m) following the methods outlined by Gustafsson et al (2019a). Hosts were identified using MacKinnon and Phillipps (2000) or Arlott (2017); host taxonomy has been updated to conform with Clements et al (2021).…”
Section: Methodsmentioning
confidence: 99%